Accelerated C♯ 2010 - Nash, Trey (Expert's voice in C#., 2010)
C♯ 2010 offers powerful new features, and this book is the fastest path to mastering them-and the rest of C♯-for both experienced C♯ programmers moving to C♯ 2010 and programmers moving to C♯ from another object-oriented language. Many books introduce C♯, but very few also explain how to use it optimally with the .NET Common Language Runtime (CLR). This book teaches both core C♯ language concepts and how to wisely employ C♯ idioms and object-oriented design patterns to exploit the power of C♯ and the CLR. This book is both a rapid tutorial and a permanent reference. You'll quickly master C♯ sy.